Mass spectrometry dataset of conventional and organic tempe before and after in vitro digestionMendeley Data - Nurul Syahidah Mio Asni; Norazlan Mohmad Misnan; Ahmed Mediani; Ivana Nur Allisya Rozlan; Nurul Amalia Zahari; Syarul Nataqain Baharum; Nurkhalida Kamal (Data in Brief, 2025)
Tempe is a superior plant-based protein source that provides a diverse array of nutritional benefits as a result of the presence of bioactive metabolites. Nevertheless, there is a scarcity of information regarding the metabolomics profile between organic and conventional tempe and the fate of these metabolites after in vitro digestion. This report examines the metabolomic profile of soybean as raw material and tempe prior to and following the in vitro digestion process. We obtained a comprehensive set of metabolomic data using ultra-high-performance liquid chromatography coupled with high-resolution mass spectrometry (UHPLC-HRMS). The metabolomics dataset organized into Excel sheets and structured according to polarity, mass to charge ratio (m/z), retention time, feature name, biological replicates and controls. This data offers preliminary insights into the metabolite profile of tempe samples, encompassing source material soybean, tempe, and tempe digesta.